(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The present work emphasizes the comprehensive ethano-medicinal uses of Blepharis edulis, to enlighten its phytochemical constituents and pharmacological uses which may useful in various types of diseases. Theo bjective of the present study was to evaluate the antioxidant and anti-inflammatory activity of extract of Blepharis edulis leaves and seeds extract for scientific validation of the folklore claim of the plant.